POTENSI MANFAAT DAN PROBLEM DI E-COMMERCE - Herma Pribadi2 (Jurnal SIGMA, 2019)
The advanced technology of internet has brought the new way of business by introduction of the e-commerce. Nevertheless, it has potential impact on both ways, positive and negative. From the positive side, it can be utilised to enhance overall company’s performance. However, it has a lot of potential problems as well, such as cybertax, security and audit trail. Therefore, everyone who involves in the e-commerce should account for those issues to reduce or mitigate its impact. Keywords: Audit Trail, Internet, Electronic Commerce